2015
DOI: 10.1123/tsp.2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Cliques in Sport: Perceptions of Intercollegiate Athletes

Abstract: Although cliques are often referenced in sporting circles, they have received little attention in the group dynamics literature. This is surprising given their potential influence on group-related processes that could ultimately influence team functioning (e.g., . The present study examined competitive athletes' perceptions of cliques using semistructured interviews with 18 (nine female, nine male) intercollegiate athletes (Mage = 20.9, SD = 1.6) from nine sport teams. Athletes described the formation of cliqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
0
20
1
Order By: Relevance
“…Despite the fact that the development of friendship groups is a normal part of sport and adolescent life (Martin et al, 2015), in this study, there was a strong discordance between coach/parent and athlete views of social media and electronic communication, with coaches and parents referring to social media subgroups as cliques. Parent and coaches' concerns are warranted, as there is some evidence that social media can have a negative impact on adolescent relationships with consequences such as cyberbullying and social isolation (Allen et al, 2014;Valkenburg & Peter, 2013).…”
Section: Discussioncontrasting
confidence: 64%
“…Despite the fact that the development of friendship groups is a normal part of sport and adolescent life (Martin et al, 2015), in this study, there was a strong discordance between coach/parent and athlete views of social media and electronic communication, with coaches and parents referring to social media subgroups as cliques. Parent and coaches' concerns are warranted, as there is some evidence that social media can have a negative impact on adolescent relationships with consequences such as cyberbullying and social isolation (Allen et al, 2014;Valkenburg & Peter, 2013).…”
Section: Discussioncontrasting
confidence: 64%
“…The authors also reported the connotation of cliques as negative subgroups. Based on the previous findings identifying the potential for subgroups to be inclusive or problematic demonstrating exclusionary behaviours resulting in the debilitative outcomes to the individual and team (Martin et al, 2015), the off-ice and clique findings reported by the female athletes in the present study were problematic decreasing ingroup ties.…”
Section: Discussionmentioning
confidence: 53%
“…The presence of greater covert, verbal antisocial behaviour and cliques in females particularly in off-ice settings and cliques was also particularly notable in conjunction with recent work on the facilitative and debilitative consequences of subgroups in sport (Martin, Evans, & Spink, 2016;Martin, Wilson, Evans, & Spink, 2015). In their discussion of coaches' and athletes' perceptions of subgroups, Martin and colleagues (2015) identified both positive (e.g., motivation, support) and negative outcomes associated with subgroups.…”
Section: Discussionmentioning
confidence: 85%
“…First, how might the presence of cliques within a sport team (e.g., Martin, Evans, & Spink, 2016; Martin, Wilson, Evans, & Spink, 2015) impact perceived intrateam communication? For example, the presence of cliques within a team may limit the communication outside of one’s subgroup within the larger team or alter the way communication is perceived inside and outside of the same clique.…”
Section: Discussionmentioning
confidence: 99%